Ideas of Islamic Education Thought KH. Ahmad Dahlan - Siti Isnaini; Islah Gusmian (al-Afkar, Journal For Islamic Studies, 2025)
At the beginning of the 20th century, Indonesia had an education system that was secular and traditional. Secular education is an educational system established by the Dutch East Indies government. In this system, only general knowledge is taught. Meanwhile, traditional education is an educational system founded by ulama, where in this system only religious knowledge is taught. This shows that education in Indonesia has not achieved its true goals. The aims of education include enlightening the life of the nation and developing the whole person, namely a person who is virtuous, has good morals, has knowledge, skills, physical and spiritual health, a stable and independent personality, and a sense of social and national responsibility. KH. Ahmad Dahlan, the founder of Muhammadiyah, attended because of his disagreement with the education system created by the Dutch East Indies government. Therefore KH. Ahmad Dahlan offers an education system that collaborates the secular education system with the traditional education system.